Causal relationship between PCSK9 inhibitor and primary glomerular disease: a drug target Mendelian randomization study - Duan, Hangyu; Shi, Yue; Zhang, Qi; Shi, Xiujie; Zhang, Yifan; Liu, Jing; Zhang, Yu (Frontiers in Endocrinology, 2024)
Background Successive observational studies have highlighted low-density lipoprotein cholesterol (LDL-C) as a standalone risk factor for the progression of chronic kidney disease (CKD) to end-stage renal disease. Lowering LDL-C levels significantly reduces the incidence of atherosclerotic events in patients with progressive CKD. Recent research indicates that proprotein convertase subtilisin kexin 9 (PCSK9) inhibitors not only effectively lower LDL-C levels in CKD patients but also exhibit therapeutic potential for autoimmune diseases such as systemic lupus erythematosus, rheumatoid arthritis, and ulcerative colitis. However, the role of PCSK9 inhibitors (PCSK9i) in treating CKD beyond lowering LDL-C levels remains uncertain. Therefore, this study employs drug-targeted Mendelian randomization (MR) to investigate the causal impact of PCSK9i on primary glomerular diseases such as IgA nephropathy (IgAN), membranous nephropathy (MN), and nephrotic syndrome (NS). Methods Single-nucleotide polymorphisms (SNPs) linked to LDL-C were sourced from the Global Lipids Genetics Consortium genome-wide association study (GWAS). Genes situated in proximity to 3-Hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR), and PCSK9 served as proxies for therapeutic inhibition of these targets. The causal link between PCSK9i and the risk of primary glomerular disorders was discovered using drug-target MR studies. The HMGCR inhibitor, a drug target of statins, was utilized for comparative analysis with PCSK9i. Primary outcomes included the risk assessment for IgAN, MN, and NS, using the risk of coronary heart disease as a positive control. Results The inhibition of PCSK9, as proxied genetically, was found to significantly reduce the risk of IgAN [odds ratio, OR (95% confidence interval, CI) = 0.05 (−1.82 to 1.93), p = 2.10 × 10−3]. Conversely, this inhibition was associated with an increased risk of NS [OR (95% CI) = 1.78 (1.34–2.22), p = 0.01]. Similarly, HMGCR inhibitors (HMGCRi) demonstrated a potential reduction in the risk of IgAN [OR (95%CI) = 0.0032 (−3.58 to 3.59), p = 1.60 × 10−3). Conclusions PCSK9i markedly decreased the risk of IgAN, suggesting a potential mechanism beyond their primary effect on LDL-C. However, these inhibitors were also associated with an increased risk of NS. On the other hand, HMGCRi appears to serve as a protective factor against IgAN. Conversely, PCSK9i may pose a risk factor for NS, suggesting the necessity for cautious application and further research into their impacts on various glomerular diseases.